(16b-6)-5(3b+3)=-3

Simple and best practice solution for (16b-6)-5(3b+3)=-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (16b-6)-5(3b+3)=-3 equation:


Simplifying
(16b + -6) + -5(3b + 3) = -3

Reorder the terms:
(-6 + 16b) + -5(3b + 3) = -3

Remove parenthesis around (-6 + 16b)
-6 + 16b + -5(3b + 3) = -3

Reorder the terms:
-6 + 16b + -5(3 + 3b) = -3
-6 + 16b + (3 * -5 + 3b * -5) = -3
-6 + 16b + (-15 + -15b) = -3

Reorder the terms:
-6 + -15 + 16b + -15b = -3

Combine like terms: -6 + -15 = -21
-21 + 16b + -15b = -3

Combine like terms: 16b + -15b = 1b
-21 + 1b = -3

Solving
-21 + 1b = -3

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '21' to each side of the equation.
-21 + 21 + 1b = -3 + 21

Combine like terms: -21 + 21 = 0
0 + 1b = -3 + 21
1b = -3 + 21

Combine like terms: -3 + 21 = 18
1b = 18

Divide each side by '1'.
b = 18

Simplifying
b = 18

See similar equations:

| 5(x-4)+3x-9x=6-(2x-5)+8x | | 0.6x+0.8660y-784.8=0 | | x*x-2=11 | | -5+3v=3v-5 | | 2x+7y=18 | | X-5=-54 | | 9s+12s+4=0 | | -13+5x=4x-7-2 | | 4x-17=4x+16 | | d=4.7+2.8(7.4) | | x*x-2=31 | | 6n+8=6n | | 8y+8=7y-2 | | -8x-x=-16-x | | d=4.7+2.8(12) | | 15+5m=-1+3m | | -3-6v=-v-6v | | =.8(x-25) | | 2.10+12.99b=12.39 | | -9+2k=-2k+7k | | -8a+6a=-2-4a | | 8n-4=-4+8n | | 4cosx+3sinx=y | | 5(X-15)2=75 | | 2a-4+2a=-12+3a | | n+8+2n-4=7+4n-20 | | x+2(-2)=-1 | | 8(4+7n)-6n=332 | | 6=k+7 | | 5x+5-6x=-x+5 | | y-5/y=10/8 | | m-15/4-4m-4/5=2 |

Equations solver categories